Programming Microsoft's Clouds : Windows Azure and Office 365. - Rizzo, Thomas (John Wiley & Sons, 2012)
A detailed look at a diverse set of Cloud topics, particularly Azure and Office 365More and more companies are realizing the power and potential of Cloud computing as a viable way to save energy and money. This valuable book offers an in-depth look at a wide range of Cloud topics unlike any other book on the market. Examining how Cloud services allows users to pay as they go for exactly what they use, this guide explains how companies can easily scale their Cloud use up and down to fit their business requirements. After an introduction to Cloud computing, you'll discover how to prepare your en.